Perceiving Ecotourism Awareness under Regulatory Fit, Volunteering Experience and Lifestyle - Husna Putri Pertiwi; Ridha Azka Raga; Jasrial; Syafiqoh Nurhayati; Dwikora Harjo (Yayasan Ilomata, 2023)
Indonesia has high potencies of ecotourism attractions, including its natural biodiversity and traditional values spreading in various regions of the archipelagos. However, the shortcoming remains exhibited by many individuals showing poorly pro-environment behavior in tourism places regarding to environmentally and socially. Therefore, our study aims to observe the effect of regulatory fit manipulation (promotion-focus vs. prevention-focus) on increasing emotional involvement to improve ecotourism awareness and examine the antecedent factors that influence individuals’ attitudes towards ecotourism attitudes, which are volunteering experience and consumptive lifestyle. This research is conducted by experimental research to examine two groups of participants under different regulatory fit manipulations (promotion-focus vs. prevention-focus). Data were analyzed by using the multivariate analysis method. Our study revealed that regulatory fit manipulation affects attitudes towards ecotourism, especially under different volunteering experiences and consumptive lifestyles. Thereby, we reveal that embodying regulatory fit for such an environmental campaign effectively enhances consumers’ attitudes toward pro-environmental and ecotourism.